2004
DOI: 10.1136/bmj.37939.570104.ee
|View full text |Cite
|
Sign up to set email alerts
|

Autopsy after termination of pregnancy for fetal anomaly: retrospective cohort study

Abstract: Objective To study trends in termination of pregnancy for fetal anomaly over 10 years and to assess the contribution of autopsy to the final diagnosis and counselling after termination. Design Retrospective study with cases from a congenital anomaly register and a defined unselected population. Data sources Pregnancies resulting in termination for fetal anomaly identified from the Oxford congenital anomaly register. Details about the prenatal diagnosis and autopsy findings were retrieved from case notes. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
118
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(131 citation statements)
references
References 9 publications
10
118
1
Order By: Relevance
“…Central nervous system anomalies accounted for more than half of the indications for both early and late terminations. This finding is consistent with the studies which showed that central nervous system malformations are the most common structural malformations leading to the TOP (4,7,8,12,13). Fetal autopsy has a particularly valuable role in the counseling of families after the TOP (14).…”
Section: Discussionsupporting
confidence: 81%
“…Central nervous system anomalies accounted for more than half of the indications for both early and late terminations. This finding is consistent with the studies which showed that central nervous system malformations are the most common structural malformations leading to the TOP (4,7,8,12,13). Fetal autopsy has a particularly valuable role in the counseling of families after the TOP (14).…”
Section: Discussionsupporting
confidence: 81%
“…This was comparable to previous similar studies. 4,9,18 In a 10-year retrospective study of autopsy after termination of pregnancy for fetal anomaly, the autopsy confirmed the suspected diagnosis in 72% cases and autopsy added information that lead to the refinement of risk of recurrence in 27% cases. 9 Hence, risk of recurrence based on ultrasonographic diagnosis of fetus may be erroneous in significant number of cases and autopsy of the fetus after termination of pregnancy is essential for genetic counseling.…”
Section: Discussionmentioning
confidence: 99%
“…9,19 The various options available for investigations in this situation was reviewed in a recent article. 19 Post-mortem MR imaging has a useful role in providing structural information of the central nervous system in fetuses and stillbirth neonates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a 19-non-steroid, which binds with high affinity to the progesterone receptor, thus inhibiting the effect of progesterone resulting in vascular damage, decidual necrosis and bleeding , which leads to cervical softening, increased uterine sensitivity to PG and conversion of the quiet pregnant uterus into an organ of spontaneous activity with maximal effect at 36-48 hours. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] PGs play an important role in the regulation of uterine contractility during pregnancy. 25 The receptors are present throughout the pregnancy; hence, PGs and PG analogues are effective for termination of pregnancy.…”
mentioning
confidence: 99%